2005
DOI: 10.5194/acp-5-465-2005
|View full text |Cite
|
Sign up to set email alerts
|

Eddy covariance flux measurements of biogenic VOCs during ECHO 2003 using proton transfer reaction mass spectrometry

Abstract: Abstract. Within the framework of the AFO 2000 project ECHO, two PTR-MS instruments were operated in combination with sonic anemometers to determine biogenic VOC fluxes from a mixed deciduous forest site in North-Western Germany. The measurement site was characterised by a forest of inhomogeneous composition, complex canopy structure, limited extension in certain wind directions and frequent calm wind conditions during night time. The eddy covariance (EC) technique was applied since it represents the most dire… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
275
11
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 213 publications
(299 citation statements)
references
References 33 publications
12
275
11
1
Order By: Relevance
“…This light and temperature dependence of monoterpene emissions by F. sylvatica L., with emissions close to zero at darkness, is in agreement with what has been reported previously by several authors (Schuh et al, 1997;Spirig et al, 2005;Holzke et al, 2006;Moukhtar et al, 2005;Dindorf et al, 2006). In the beginning and at the end of the experimental period the emission rate at zero PPFD was found to be negligible.…”
Section: Nighttime Emissions and Standard Emission Factorssupporting
confidence: 81%
See 1 more Smart Citation
“…This light and temperature dependence of monoterpene emissions by F. sylvatica L., with emissions close to zero at darkness, is in agreement with what has been reported previously by several authors (Schuh et al, 1997;Spirig et al, 2005;Holzke et al, 2006;Moukhtar et al, 2005;Dindorf et al, 2006). In the beginning and at the end of the experimental period the emission rate at zero PPFD was found to be negligible.…”
Section: Nighttime Emissions and Standard Emission Factorssupporting
confidence: 81%
“…(2)) inferred from the measured monoterpenoid emission rates of the second tree are found to vary between 100 and 1550 mg m À2 h À1 or 2 and 32 mg g DW À1 h À1 , in good agreement with literature data reported for F. sylvatica L. in recent years (Schuh et al, 1997;Kahl et al, 1999;Spirig et al, 2005;Moukhtar et al, 2005;Dindorf et al, 2006), which have been recently compiled in Table 3 of Dindorf et al (2006), and with the values adopted in the two most recent European plant-specific BVOC inventories, 22.1 mg g DW À1 h À1 (Karl et al, 2009) and 10.0 mg g DW À1 h À1 (Schurgers et al, 2009). …”
Section: Nighttime Emissions and Standard Emission Factorssupporting
confidence: 79%
“…26,27 Quality assurance of the fluxes was performed by removing data that failed the criteria for turbulence (friction velocity below 0.15 m s −1 ) or stationarity (when the stationarity test, calculated on 5 min subperiods, for the various BVOC fluxes exceeded 60% as defined by Foken and Wichura 28 ). In total, also including instrument failures, we gap-filled about 60% of the data set, mainly during the night hours.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Forests emit large quantities of monoterpenes. For example average daytime monoterpene emissions of 2.2 nmol m −2 s −1 were reported for a mixed deciduous forest [Spirig et al, 2005]. During warm days, Grabmer et al [2004] reported monoterpene emission fluxes up to 2.5 nmol m −2 s −1 over a Norway Spruce forest using the relaxed eddy covariance method.…”
Section: Deposition Fluxes Of Monoterpenesmentioning
confidence: 99%